Acidity of unstimulated saliva and dental plaque in asthmatics, treated with inhaled corticosteroids and long-acting sympathicomimetics. - Emilia Karova; George Christoff (Peytchinski Publishing, 2012)
The number of asthmatics is continuously increasing all over the world. The aim of the study is to study the effect of different combinations of inhaled corticosteroids and long-acting sympathicomimetics on salivary and plaque pH in asthmatics with mild persistent asthma. The effect of different quantities of lactose, as gustatory corrector in the inhalers, is traced out.Thirty patients of both sexes, from 20 to 55 years old participated in the study. Salivary and plaque pH values are traced out in 30 minutes period after drug inhalation, at 6-months interval. It is found out that inhaled drugs cause significant decrease of initial salivary pH values, the lowest ones reported on first and fifth minute after the inhalation. The average salivary pH levels on the 30th minute remain significantly lower than initial ones.Most considerable changes in pH values are registered for patients treated with Fluticasone propionate and Salmeterol.